2013
DOI: 10.1186/1471-2407-13-159
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound real-time elastography can predict malignancy in BI-RADS®-US 3 lesions

Abstract: BackgroundLesions of the breast that are classified BI-RADS®-US 3 by ultrasound are probably benign and observation is recommended, although malignancy may occasionally occur.In our study, we focus exclusively on BI-RADS®-US 3 lesions and hypothesize that sonoelastography as an adjunct to conventional ultrasound can identify a high-risk-group and a low-risk-group within these patients.MethodsA group of 177 breast lesions that were classified BI-RADS®-US 3 were additionally examined with real-time sonoelastogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 21 publications
2
33
1
3
Order By: Relevance
“…Thereby, the subgroup of lesions that has a very low risk (<2%) of being malignant, namely BI-RADS 3, can be separated from the higher risk groups and short-interval follow-up can be offered instead of biopsy. Although cancer incidence among BI-RADS 3 masses is reported to be independent of larger size, advanced age, and palpability, in our practice and in many others, patients with these features are referred for biopsy instead of follow-up (17)(18)(19). In our limited study, none of the probably benign masses that were referred for biopsy due to such relative risk factors took a malignant diagnosis.…”
Section: Discussionmentioning
confidence: 67%
“…Thereby, the subgroup of lesions that has a very low risk (<2%) of being malignant, namely BI-RADS 3, can be separated from the higher risk groups and short-interval follow-up can be offered instead of biopsy. Although cancer incidence among BI-RADS 3 masses is reported to be independent of larger size, advanced age, and palpability, in our practice and in many others, patients with these features are referred for biopsy instead of follow-up (17)(18)(19). In our limited study, none of the probably benign masses that were referred for biopsy due to such relative risk factors took a malignant diagnosis.…”
Section: Discussionmentioning
confidence: 67%
“…Primary breast cancer and other metastatic disease to the breast are most often more stiff than the surrounding tissue on sonoelastography. [5][6][7]18 Several parameters have been used to predict malignancy when using US elastography. E/B ratio, the comparison of the lesion size on elastography to B-mode US, has been used to predict malignancy, with E/B ratios greater than 1 favoring malignancy.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…In the recent years, elastography has proven to be an effective additional imaging modality when studying breast cancer, particularly primary breast cancer. [5][6][7] Gkali et al 8 reported a case of primary non-Hodgkins lymphoma of the breast that demonstrated increased stiffness on strain elastography. However, Barr et al 9 has reported a case of breast lymphoma that was soft on both SE and SWE.…”
mentioning
confidence: 98%
“…The difference in specificity was most probably caused by false negative results in the color map mode: borderline lesions that are too hard to be a plain ES=3 score on the color map, but not hard enough for a score of 4. Some authors have stated that benefits of the RTE technique are seen in cases that have benign US characteristics, are classified as BI-RADS -US 3, and show increased hardness on elastography [30] and thus are reclassified in the BI-RADS -US 4 category [31].…”
Section: Discussionmentioning
confidence: 99%